2003
DOI: 10.1080/07481180302899
|View full text |Cite
|
Sign up to set email alerts
|

Death of an Abuser: Does the Memory Linger On?

Abstract: Although the fields of bereavement and traumatology regarding childhood physical and sexual abuse have developed simultaneously, little information exists regarding the issues of bereavement for a sexual abuse survivor when the decedent was the abuser. This article is a case study that examines the reactions, themes, and attributions that individuals experience regarding the loss of a relative who was sexually abusive to them during childhood and discusses the impact of that abuse on the bereavement process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…CSA survivors reported ambivalent and contradictory grief reactions that paralleled their love-hate relationships with their abusers. Similar to Monahan's (2003) findings, common grief reactions included confusion, sadness, relief, and anger. Most participants also indicated initial reactions of shock and an inability to process emotions, but few reported the guilt and embarrassment reported in Monahan's case study.…”
Section: Grief Experiences Of Csa Survivorssupporting
confidence: 68%
See 2 more Smart Citations
“…CSA survivors reported ambivalent and contradictory grief reactions that paralleled their love-hate relationships with their abusers. Similar to Monahan's (2003) findings, common grief reactions included confusion, sadness, relief, and anger. Most participants also indicated initial reactions of shock and an inability to process emotions, but few reported the guilt and embarrassment reported in Monahan's case study.…”
Section: Grief Experiences Of Csa Survivorssupporting
confidence: 68%
“…Our review of the existing empirical literature revealed only two articles that directly addressed grief experiences after sexual abusers died. Monahan (2003) described, in a case study, the complex nature of one U.S survivor’s grief following the death of her abusive brother. The survivor experienced conflicting and confusing emotions and exhibited emotions such as rage, depression, guilt, sorrow, and embarrassment.…”
Section: Csa Survivors and Griefmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the task of mourning and letting go may be the most arduous of all the struggles that the survivor endures. Monahan (2003) indicates that the lack of resolution regarding the abuse before the perpetrator dies can complicate treatment. Two survivors reported that their brothers died without ever discussing the abuse, and had never indicated any remorse or regret about their behavior.…”
Section: Mourning and Letting Gomentioning
confidence: 97%
“…Dealing with conflicted, ambivalent feelings toward parents and siblings, particularly around such issues as mourning and grief during the aging process, can present a host of therapeutic dilemmas (Monahan 2003). This paper examines the thematic treatment issues presented in a small, clinical practice setting by eight women, aged 56 through 69, who were sexually abused by their brothers or stepbrothers during childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%